2001
DOI: 10.1142/s0192415x01000381
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Sheng-Mai-San Reduces Myocardial Infarct Size Through Activation of Protein Kinase C and Opening of Mitochondrial KATP Channel

Abstract: Sheng-mei-san (SMS), a traditional Chinese formulation comprising Radix Ginseng, Radix Ophiopogonis and Fructus Schisandrae, has long been used for more than 700 years for patients with coronary heart disease. We attempted to clarify 1) whether SMS reduces myocardial infarct size, and 2) whether the infarct size-reducing effect of SMS is related to activation of protein kinase C and the opening of the mitochondrial KATP channels in Japanese white rabbits without collateral circulation. The results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Another study indicated that Xue-Fu-Zhu-Yu-Tang inhibits ischemic myocardial apoptosis, most likely through a sensitization agent that inhibits SIRT1 (silent mating type information regulation 2 homolog-1) apoptosis pathways [ 16 ]. Sheng-Mai-San could reduce myocardial infarct size through activation of protein kinase C, opening of the mitochondrial KATP channel, and reducing oxidative damage [ 17 19 ]. Dan Shen has antioxidant effects, inhibits smooth-muscle-cell proliferation, and protects against vascular atherosclerotic lesions by circulating ROS suppression via the PKC/p44/42 MAPK-dependent pathway [ 20 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that Xue-Fu-Zhu-Yu-Tang inhibits ischemic myocardial apoptosis, most likely through a sensitization agent that inhibits SIRT1 (silent mating type information regulation 2 homolog-1) apoptosis pathways [ 16 ]. Sheng-Mai-San could reduce myocardial infarct size through activation of protein kinase C, opening of the mitochondrial KATP channel, and reducing oxidative damage [ 17 19 ]. Dan Shen has antioxidant effects, inhibits smooth-muscle-cell proliferation, and protects against vascular atherosclerotic lesions by circulating ROS suppression via the PKC/p44/42 MAPK-dependent pathway [ 20 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…145: 722-7227. doi: 10.1016/j.jep.2012.11.036 Hausenloy, D.J., and Yellon, D.M. 2007 Wu et al, 2011;Xia et al, 2011 Aged rats IR P ginseng ↓infarct size, ↑LV funcƟon ↑Akt/eNOS, Sirt1 and Sirt3, ↓Erk/caspase 7 Luo et al, 2015 Guinea pig IR Korean red ginseng ↑funcƟon Antioxidant, anti-inflammatory Aravinthan et al, 2015 Rabbit IR Shreng-mai-san ↓infarct size ↑PKC, ↑mKATP Wang et al, 2001 Mouse IR Compound K ↓infarct size ↑Akt-eNOS pathway Tsutsumi et al, 2011 Rat Iso treatment Korean red ginseng ↓injury, ↑LV funcƟon Antioxidant Lim et al, 2013 Porcine Iso treatment Korean red ginseng ↓injury, ↑LV funcƟon Antioxidant Lim et al, 2014 D r a f t…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (1996) have postulated that the presence of lignan-enriched extract of Fructus schisandrae accounts for the beneficial effects of Sheng-Mai-San although others have implicated the ginsenoside content of this formulation as a basis for cardioprotection, at least in a mouse model of isoproterenol-induced cardiac injury . Sheng-Mai-San has also been shown to reduce infarct size in rabbits when administered up to three days prior to infarction, with no benefit observed with acute treatment (Wang et al 2001). The benefit was proposed to be mediated by activation of protein kinase C and opening of mitochondrial ATP-sensitive potassium channels primarily attributable to the presence of ginsenosides and lignans as the primary active ingredients in this formulation (Wang et al 2001).…”
Section: Ginsenoside-containing Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…CHM injections based on sheng mai san are also widely prescribed. It reduces infarct size via the activation of protein kinase C, opening of the mitochondrial KATP channels, and lowering the concentration of 5-hydroxytryptamine, norepinephrine, methionine-enkephalin, and leucine-enkephalin [10, 11]. …”
Section: Introductionmentioning
confidence: 99%